Technical Efficiency of the Setbag Net Fishery in Bangladesh: An Application of a Stochastic Production Frontier Model - Golam Rabbani, Md; Akhtaruzzaman Khan, Md; Serajul Islam, M; Yeasmin Lucky, Rozina (The Agriculturists, 2018)
A study was conducted to examine the technical efficiency for Setbag net fishing boats operated in the year 2014. A total of 100 samples of Setbag net fishing boats were selected, of which 40 were from Cox’s Bazar, 40 were from Chittagong and 20 were from Bagerhat. Stochastic frontier (with technical inefficiency effect) model was specified and estimated. Results have shown that the estimated mean technical efficiency of Setbag net fishing boats is 84 percent. The efficiency of Setbag net fishing boat was positively associated with total cost, while the number of nets were negatively related to fishing day and crew size. Head maji’s age had significant effect on inefficiency at 5% level. Although, the effect on boats’ efficiency was positive, (though insignificant) for head maji’s experience, head maji’s education, engine horse power and boat age. The use of modern fishing boat and improved fishing technology should be promoted, through proper training and motivation program for fisher. At the same time old and unfit fishing boat and gears should be gradually removed and replaced by new and modern fishing boat. The Agriculturists 2017; 15(2) 59-65